Sabour Makhana-1: A new makhana variety - KUMARI, Anil; Yadav, Pankaj Kumar; Nath, Paras; Patel, V B; Kumar, Rajesh (Indian Horticulture, 2020)
Sabour Makhana-1 was developed at Bhola Paswan Shastri Agricultural College, Purnea of Bihar Agricultural University, Sabour, Bhagalpur, Bihar, India and was released by State Varietal Release Committee, Bihar on 29 August 2016. Sabour Makhana-1 is characterized by large spherical leaves, dark purple flower, medium size fruits, small oval seeds with very thin seed coat (0.29 mm). It is a high yielding (32-35 q/ha) variety with good quality makhana pop recovery (55-60%). It has moderate field resistance to leaf blight disease (Altenaria spp.) and important insect pests, viz. aphid (Rhopalosiphum nymphaeae), case worm (Eiophila depunctalis and E. crisonalis) and leaf midge (Chironomus spp). It is a potential variety to get the higher net return from underutilized and neglected waterlogged areas without eroding natural resources.